TUTORIAL WITH THE APPLICATION OF MATHEMATICS IN TECHNICAL COURSES - FILÍPEK, Josef; NAVRÁTIL, Miroslav (Trends in education, 2013)
Mathematics is characterized by a high level of abstraction. It is a considerable problem for students to apply differential calculus in engineering practice. The authors compiled a multimedia tutorial with commentaries concerning the relationship of instantaneous position, velocity, and acceleration of a vehicle with the application of the first and second derivatives of the primary function. This teaching tool illustrates the concepts such as decreasing and increasing functions, concave and convex functions, local extrema, inflection points, domains of functions, etc.
Keywords: differentiation; movement; graphs of functions; tutorial